WITRICITY (WIRELESS ELECTRICITY): Aas Wasri Hasanah, Oktaria Handayani - Jurnal, Redaksi Tim (SUTET, 2018)
Electricity is an integral part of every human being and power transmission by wires is a necessityto fulfill the need of electricity. ‘What if we can come out of this tangled wire-theory?’- With this view, Nikola Tesla introduced the concept of wireless power transfer in early 20th century. Wireless Power Transfer (WPT) is not only reliable and efficient but it is also eco-friendly and cost effective. A lot of concepts for WPT are already discussed by researchers, scientists and inventors. In addition to the available works and principles, this paper explains the basic concept, design and implementation of wireless electricity with magnetic induction technique and determining its practical result carried out with the same.